FLORISTIC AND PHYTOSOCIOLOGICAL COMPOSITION OF THE SQUARES IN THE CITY OF SANTARÉM, PARÁ - Gomes de Sousa Oliveira, Thiago; Biondi, Daniela; Cristo de Almeida, Everton; Santos de Sousa, Verena; Fernandes da Silva, Ádria; Nunho dos Reis, Allan Rodrigo (Floresta, 2024)
The vegetation composition in green areas plays an important role in obtaining ecosystem benefits within these spaces. Therefore, this research aimed to characterize the floristic and phytosociological composition of the tree canopy in the squares of Santarém, Pará. To achieve this, a floristic survey was conducted in 38 squares, considering trees with a height greater than 1.5 m. Taxonomic and phytogeographical information of the trees was identified, and phytosociological parameters such as frequency (AF and RF), density (AD and RD), dominance (ADo and ADr), cover value index (CVI), importance value index (IVI), and Shannon-Wiener diversity index (H’) were evaluated. A total of 686 trees were identified, with 54.60% of them being native species of Brazil and 45.40% exotic to the country. The Fabaceae family stood out with the highest number of species (19), while Anacardiaceae had the highest number of individuals (219). The species with the highest Af and Rf were Mangifera indica (78.95 - 14.71%) and Moquilea tomentosa (43.74 - 8.33%), and for Da and Dr, Mangifera indica (10.51 - 27.16 ind/ha) and Azadirachta indica (4.72 - 12.21 ind/ha) were prominent. In terms of DoA and DoR, Mangifera indica (7.85 - 48.48 m2/ha) and Spondias mombin (1.67-10.32 m2/ha) were highlighted. In IVI, M. indica also stood out (90.34%). The overall H’ for the squares was 2.85, with Parque da Cidade (2.85) and Jati (2.23) squares being the most prominent. Only two squares showed moderate to high diversity (H’ > 2.22). The floristic composition is predominantly composed of exotic individuals (54.60%), especially the species M. indica.